Proposed guidelines for the construction of theses abstracts of the University of the Philippines' Institute of Library and Information Science - Tenmatay, Tyran Rex; Castillo, Africa R. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2006)
An abstract is a brief summary of the research. A summary however brief, contains the most important aspects of study done by students and professional researchers alike. To better serve the researchers, a uniform abstracting guideline needed to be created to replace the too simple, "not to exceed 2 pages" used by the Institute of Library and Information Science Thesis/Special Problem Manual dated July 2003.This study did a user needs assessment of the students of the Institute of Library and Information Science in relation to their theses abstracting needs and expectations by using a checklist questionnaire. The data gathered was then presented to a professional abstractor and refined into a more concrete guideline specifying the content and length of the abstract.
The responses and the views of the abstractor centered in the importance of the Statement of the Problem, Summary and Conclusion and Recommendations, Significance of the Study, Analysis and Interpretation of Data, and the Research Design and Instrument used and having an ideal length of 250-500 words.
Also seen in the survey were inconsistent responses, which led to the additional recommendation that the Institute either increase the teaching of abstracting or its separation from the indexing course thus allowing more students to experience it more fully. Another option would be a short refresher for those taking the LIS 199 and 299 courses.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines Institute of Library and Information Science; Dissertations, Academic -- Abstracts